THE EFFECT OF WATER REDUCTION IN KRAFT PULP WASHING IN ECF BLEACHING - Frigieri, Tania Cristina [UNESP]; Ventorim, Gustavo [UNESP]; Comelato Favaro, Jaqueline Silveira [UNESP] (Univ Federal Vicosa, 2016)
The main objective of this work was to study the technical viability of using the cellulose bleaching effluent, at several stages of the process, seeking fresh water reduction in pulp washing, and evaluating its effect on pulp quality. Eucalyptus spp. industrial cellulosic pulp with oxygen was used in this experiment. The same bleaching sequence D(E+P) DP was performed ten times, under the same conditions (temperature, consistency and time). Counter current washing was used in the bleaching stages, and each sequence was carried out with different washing factors: 9, 6, 3, 0 m(3) of distilled water/ton of pulp, trying to reach brightness of 92 +/- 0,5% ISO. The ten sequences sought to achieve the stability of the effluent organic load, measured by the chemical oxygen demand (COD). Then, the COD results were compared to the brightness ones from the bleached pulp. The evaluated results from the ten sequences and four different washings showed an increasing in COD due to the organic load accumulation, resulting from the reuse of effluent from previous sequences. This COD increasing provided the lower brightness results during the cycles, besides the water reduction, evidencing the necessity of washing between bleaching stages. In this study, the obtained result for the pulp washing up to 3m(3)/t was tolerable and even recommended. On the other hand, the pulp without any washing (0 m(3)/t), due to the lack of enough brightness, it is commercially unviable.
Keywords: Pulp; Bleaching; Eucalyptus